2022
DOI: 10.2147/idr.s371411
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pyogenic Spondylitis Caused by Streptococcus Constellatus in an Obese Patient: A Case Report

Abstract: Streptococcus constellatus ( S. constellatus ) is a well-known part of the normal flora in humans. Pyogenic spondylitis (PS) induced by S. constellatus is very rare. In this case, a 46-year-old male patient presented to our hospital with a 2-month history of low back pain and weakness in both legs. Based on his clinical manifestations, laboratory findings, blood culture results, imaging and histopathological findings, the patient was diagnosed with PS ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Streptococcus constellatus is an extremely rare SEA pathogen with only a few cases. For instance, Dai et al reported that a 58-year-old female had SEA caused by Streptococcus constellatus infection, 7 Korugan et al reported invasive suppurative spondylitis caused by Streptococcus constellatus infection, 8 Jin et al reported another obese patient with acute suppurative spondylitis caused by Streptococcus constellatus , 3 and Takada et al reported a rare case of suppurative thrombophlebitis of the posterior neck caused by Streptococcus constellatus . 9 All of these patients recovered after surgery and 6–8 weeks of systemic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Streptococcus constellatus is an extremely rare SEA pathogen with only a few cases. For instance, Dai et al reported that a 58-year-old female had SEA caused by Streptococcus constellatus infection, 7 Korugan et al reported invasive suppurative spondylitis caused by Streptococcus constellatus infection, 8 Jin et al reported another obese patient with acute suppurative spondylitis caused by Streptococcus constellatus , 3 and Takada et al reported a rare case of suppurative thrombophlebitis of the posterior neck caused by Streptococcus constellatus . 9 All of these patients recovered after surgery and 6–8 weeks of systemic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…9 All of these patients recovered after surgery and 6-8 weeks of systemic antibiotics. 3 The diagnosis of SEA needs to be made carefully, and a correct diagnosis is crucial to the treatment of SEA. As we reported in this case, his clinical symptoms (high fever, limb paraplegia, motor sensory dysfunction, urination and defecation dysfunction) were not specific, and there are similar manifestations in other diseases, such as cervical spondylotic myelopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, and based on the review of the published literature, similar cases of pyogenic paracostal and paravertebral abscesses were not yet described. There are only a handful of case reports reporting pyogenic spondylitis caused by SC [ 10 , 11 , 12 , 13 , 14 ]. The case that was similar the most in the published literature was by Jin and Yin in which they presented a patient diagnosed with pyogenic spondylitis caused by SC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a handful of case reports reporting pyogenic spondylitis caused by SC [ 10 , 11 , 12 , 13 , 14 ]. The case that was similar the most in the published literature was by Jin and Yin in which they presented a patient diagnosed with pyogenic spondylitis caused by SC [ 10 ]. That patient was of similar age as the patient in our case report; however, he was male and obese, with a body mass index (BMI) of over 40 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%